Conscientious objection: between freedom and rights - Robledo, Paz (Revista Chilena de Salud Pública, 2019)
Chile’s Law 21.030 decriminalized the voluntary interruption of pregnancy in three situations (when the woman’s life is at risk, where the fetus has a lethal malformation, and in pregnancies resulting from rape), and also, for the first time in national legislative history, introduced the right to conscientious objection for clinical teams that participate directly in abortion procedures for the three situations considered in the Law. This Law spurred a broad social and legislative debate, and one year after its implementation, it is concerning to observe that the clinical teams’ conscientious objections have been principle barrier impeding women’s access to these health benefits, despite their legal right. This article seeks to contribute to the national debate on the role of health professionals in this new legal-sanitary scenario, where the balance between the personal freedoms of professionals and the legitimate right of women to access the services defined in Law 21.030 are at the center of the discussion. These are expressed either as an opportunity or as a definitive threat to the rule of law, which is to say, to our democracy.